Development of energy analyzer of charged particles based on the basis non-uniform electrostatic field - Saulebekov, A.О.; Vénos, D.; Kambarova, Z.T.; Saulebekova, D.A.; Vassilyeva, K.I.; Seidualy, K.B. (Eurasian Physical Technical Journal, 2019)
The electron-optical characteristics of a mirror energy analyzer based on a non-uniform, hyperbolic decreasing electrostatic field were investigated. In work an approximate-analytical method for calculating the trajectory of charged particles in an electrostatic field, acting in the mirror reflection regime, was used. The equation of motion of charged particles in the integro-differential form is obtained. The scheme of the most optimal variant of the analyzer with a non-uniform field is found.
Keywords: non-uniform field; energy analyzer; mirror reflection regime; electron-optical characteristics; trajectory of charged particles